THE DESIGN OF ELECTROLYTE AND NON ELECTROLYTE SOLUTION TEACHING MATERIALS WITH MULTI REPRESENTATION - Isma Dwi Sundari; Dewi Nurdiyanti; Indah Karina Yullina; Tania Ivanda Gusman (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2021)
The limited resources for learning chemistry and the lack of application of multiple representations in schools are a problem for students in understanding chemistry at the molecular level. This study aims to obtain a multi-representation-oriented teaching material design that is feasible to use. Development of teaching materials using the 4D Thiagarajan et al, this is because this model is specifically for book development. The design of electrolyte solution and multi-representation-oriented teaching materials is assessed by five experts consisting of three FKIP lecturers and two chemistry teachers. The results of judgment on aspects of material feasibility, presentation of material, and language each get a percentage of 83%; 83.%; 83.9% the three into the very decent category. While the results of the multi-representation aspect of judgment consist of five criteria, namely 1) the type of representation, the type of representation (C1), the interpretation of features (C2), the relationship with the text (C3), the description of the image (C4), the degree of connectedness (C5) has been met according to the criteria specified used. In the readability test, the teaching materials developed are categorized as easy to understand for students and independent categories, then received a positive response from students.